P297 PERICARDIAL EFFUSION WITHOUT HEMODYNAMIC INSTABILITY: WHEN AND TO WHOM THE PERICARDIOCENTESIS?. (18th May 2022) - Facchini, E; Maffè, S; Paffoni, P; Prenna, E; Bergamasco, L; Careri, G; Franchetti Pardo, N; Paino, A; Dellavesa, P
Abstract: Cardiac tamponade is traditionally considered a clinical diagnosis, but there are pre–tamponating effusions that occur without signs of cardiogenic shock, and in these situations it can be complex to determine when and which patient treat with pericardiocentesis. The clinical case concerns a 90–year–old woman who comes to the emergency room for exertional dyspnea. Upon arrival blood pressure was 150/90 mmhg, heart rate 70 bpm. On chest x–ray, enlargement of the cardiac silhouette was evident (Fig 1 ). The echocardiogram showed a circumferential pericardial effusion of 2 centimeters with signs of right cardiac chambers compression (Fig 2 ). Hospitalized in ICU, the clinical situation was complicated by the onset of atrial fibrillation with a high ventricular response (Fig 3 ) and immediate cardiogenic shock (BP 70/40 mmHg, tachypnea, altered mental status). We proceed with emergency electrical cardioversion, effective in restoring sinus rhythm with almost immediate arrhythmic recurrence; therefore we perform a pericardiocentesis, with regression of the shock status after aspiration of a few cc of serum–haematic pericardial fluid (total 750 cc); spontaneous restoration of sinus rhythm after the procedure. Neoplastic problems were excluded, IgM positivity for influenza A and B on blood tests. The patient presented no further complication, was discharged at home, in sinus rhythm, with negative follow–up so far. This clinical case focuses the question of the indication and timing of pericardiocentesis. We managed a pericardial effusion with ultrasound signs of compression of the right sections, but in the absence of clinical signs of cardiogenic shock / Beck's triad. Given the clinical evolution, should we have perform the pericardiocentesis as soon as the patient arrived, in conditions of hemodynamic stability? Interesting are the score index proposed by Halpern et al. and an ESC position statement that serves to identify patients to undergo urgent pericardiocentesis based not only on clinical factors, but also on imaging evaluation. The total score of our case would have been indicative for an immediate pericardiocentesis. In our opinion, the formulation of a triage system for patients with pericardial effusion and hemodynamic stability that can be routinely implemented in clinical practice would be extremely useful.